PERUBAHAN TATA KELOLA PEMERINTAHAN DESA DALAM ANALISIS KETERLIBATAN POLITIK BERBASIS PEMBANGUNAN DESA YANG BERKELANJUTAN - Dewi, Kaamiliaa; Atmojo, Muhammad Eko (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to examine the technology-based community participatory approach in the context of sustainable village development. The main focus of the study is to explore the transformation of village governance with an emphasis on sustainable development aspects. The method used is descriptive qualitative with data collection or compilation through documentation. The results of the research implementation indicate that the reform of the village governance system plays an important role in achieving sustainable village development. Community involvement that pays attention to environmental aspects is the main foundation in these development efforts. It is hoped that local communities will increasingly realize the importance of protecting the environment and have the opportunity to apply sustainable practices in their daily lives. Active participation that is originally from the community in implementing decision-making and implementing village development projects is very important to ensure the sustainability of environmental protection. Environmental protection must be at the core of efforts to achieve a balance between three important things, namely growth in economic aspects, social welfare, and environmental preservation. However, changes in village governance are currently not optimal, as seen from conflicts of interest, lack of coordination between government agencies, and technical constraints in the field. This study also faces challenges in accessing secondary data on sustainable village development. Therefore, it is necessary to have a more in-depth research by considering the future aspects in sustainable village development. Input from readers is highly expected to improve the quality of the next article.